O faturamento hospitalar: quem cuida conhece? - Silva, Luís Carlos de Paula e [UNESP]; Muller, Debora Abdian; Sales, Patrícia Regina de Souza; Almeida, José Luis de; Barbosa, Pedro Marco Karan; Melo, Sandra Maria Camillo Barros de (My University, 2013)
Introduction: In hospital management control spending and increased revenues are critical to the sustainability of the organization. Objective: To assess the knowledge of health professionals who work in care in a hospital, with regard to billing of patient accounts. Method: Quantitative study that addressed health professionals in a hospital; the study population was comprised of 274 professionals. Results: 144 (64%) can define billing; 137 (60.9%) says that the billing occurs after discharge; 92 (40.9%) do not know where is the billing sector; 93 (41.3%) did not record what they performed; 216 (96%) never received training on billing; 157 (69.8%) did not know how to love handles account; 206 (91.6%) had no guidance on billing for training; 202 (89.8%) would like to have access to amounts billed; 208 (92.4%) think that knowing the amount billed would contribute in promoting strategies for cost containment; and 151 (67.1%) did not know the tables SUS. Conclusion: The study showed that physicians do not know how the billing process occurs the patient’s account.

Introdução: Na gestão hospitalar, o controle dos gastos e o incremento de receitas são fundamentais para a sustentabilidade da organização. Objetivo: Avaliar o conhecimento dos profissionais da saúde que atuam no cuidado em um hospital, no que se refere ao faturamento das contas dos pacientes. Método: Estudo quantitativo abordando profissionais da saúde em um hospital; a população do estudo foi composta por 274 profissionais. Resultados: 144 (64%) conseguem definir faturamento; 137 (60,9%) dizem que o faturamento ocorre após a alta do paciente; 92 (40,9%) não sabem onde fica o setor de faturamento; 93 (41,3%) não anotam o que realizam; 216 (96%) nunca receberam treinamento sobre faturamento; 157 (69,8%) não sabem como se processa uma conta; 206 (91,6%) não tiveram orientação sobre faturamento durante a formação; 202 (89,8%) gostariam de ter acesso aos valores faturados; 208 (92,4%) acham que conhecer o valor faturado iria contribuir na promoção de estratégias de contenção de gastos; e 151 (67,1%) não conhecem as tabelas SUS. Conclusão: O estudo mostrou que os profissionais não conhecem como ocorre o processo de faturamento da conta do paciente.
The hospital billing: who cares knows?
Keywords: Billing; Health care costs; Hospital costs; Economics, hospital; Health management; Faturamento; Custos de cuidados de saúde; Custos hospitalares; Economia hospitalar; Gestão em saúde